RELATION BETWEEN POLITICAL REPRESENTATIVES AND PEOPLE IN POWER DECENTRALIZATION (International Journal of Food and Nutritional Sciences, 2022)
The concept of decentralization refers to decentralized, directed from center to periphery, organized around and such. This concept, expressed as the transfer of authority from the center to subordinate ends, is important both for more effective and productive management of the areas outside the center organization in public administration and for strengthening these areas in terms of democracy conception. Because of the increasing interest all over the world in issues such as ensuring service–need compliance, the importance of decisions made by the closest unit to the public and the reduction of bureaucratization have made implementation of decentralized systems a necessity in local regions. In this study, conceptual definitions regarding decentralization and information about its aspects as well as the effects of political and administrative decentralization on unitary structures will be presented.